Mukhriz to be Kedah MB if BN wins - New Sunday Times, , (New Sunday Times, 2013)
KUALA LUMPUR: Datuk Mukhriz Mahathir,46, will be named Kedah menteri besar if Barisan Nasional recaptures the state today.